2012
DOI: 10.1039/c2ra20289a
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and modeling of HMX granular explosives subjected to drop-weight impact

Abstract: The drop-weight impacts on a thin layer of cyclotetramethylene tetranitramine (HMX) explosive particles have been performed. The drop-weight impact machine is equipped with high-speed photographic techniques. Effects of drop heights and the amount of particles on compaction, deformation, and thermal responses were investigated. Considering the contact plasticity, friction, melting, fracture, as well as chemical reaction, an analytical model based on heating and kinematics equations for a single layer of explos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…These debated interactions are wide‐ranging including defect and pore interactions , particle‐particle interactions , energy dissipation , and frictional heating ; however as this paper focuses on PBX samples with two or more HMX particles, the most relevant factor is the particle‐particle interactions and frictional heating. Zhou et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These debated interactions are wide‐ranging including defect and pore interactions , particle‐particle interactions , energy dissipation , and frictional heating ; however as this paper focuses on PBX samples with two or more HMX particles, the most relevant factor is the particle‐particle interactions and frictional heating. Zhou et al .…”
Section: Introductionmentioning
confidence: 99%
“…These debated interactions are wide-ranging including defect and pore interactions [6-9], particle-particle interactions [10,11], energy dissipation [12], and frictional heating [13][14]; however as this paper focuses on PBX samples with two or more HMX particles, the most relevant factor is the particle-particle interactions and frictional heating. Zhou et al looked into the surface roughness and found that there is a "statistically significant" correlation between the surface quality and the shock sensitivity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Other dynamic processes include impact, chemical reaction or ignition, and growth of hot spots. Despite extensive literature on this topic a complete understanding of all the processes and dynamics does not yet exist, especially at the particle or microstructure level [2][3][4][5][6][7][8][9][10][11][12][13]. Studies have examined a variety of sample geometries, materials, and loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that lower density samples build-up to detonation quicker and that age doesn't affect the shock wave profile [6]. Wu et al also considered the sensitivity of HMX particles by performing dropweight experiments [7]. Both single and multiple particles were tested, and it was determined that initiation sensitivity is partially dependent on particle-particle interactions.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, high-energy density compounds (HEDCs) with high positive heats of formation (HOFs), high densities (q), excellent detonation properties [detonation velocity (D) and detonation pressure (P)], good thermal stability as well as low impact, and shock sensitivities have been receiving considerable attention to meet the continuing development of national defense and economy [1][2][3][4][5]. Among various types of HEDMs, high energetic cyclic nitramines constitute a unique class of energetic materials and have played an important role in this field.…”
Section: Introductionmentioning
confidence: 99%